Rhodotorula glutinis Phenylalanine/Tyrosine Ammonia Lyase Enzyme Catalyzed Synthesis of the Methyl Ester of para-Hydroxycinnamic Acid and its Potential Antibacterial Activity - MacDonald, Marybeth C.; Arivalagan, Pugazhendhi; Barre, Douglas E.; MacInnis, Judith A.; D’Cunha, Godwin B. (Frontiers in Microbiology, 2016)
Biotransformation of L-tyrosine methyl ester (L-TM) to the methyl ester of para- hydroxycinnamic acid (p-HCAM) using Rhodotorula glutinis yeast phenylalanine/tyrosine ammonia lyase (PTAL; EC 4.3.1.26) enzyme was successfully demonstrated for the first time; progress of the reaction was followed by spectrophotometric determination at 315 nm. The following conditions were optimized for maximal formation of p-HCAM: pH (8.5), temperature (37 C), speed of agitation (50 rpm), enzyme concentration (0.080 µM), and substrate concentration (0.50 mM). Under these conditions, the yield of the reaction was ~15% in 1 h incubation period and ~63% after an overnight (~18 h) incubation period. The product (p-HCAM) of the reaction of PTAL with L-TM was confirmed using Nuclear Magnetic Resonance spectroscopy (NMR). Fourier Transform Infra-Red spectroscopy (FTIR) was carried out to rule out potential hydrolysis of p-HCAM during overnight incubation. Potential antibacterial activity of p-HCAM was tested against several strains of Gram positive and Gram negative bacteria. This study describes a synthetically useful transformation, and could have future clinical and industrial applications.